2020
DOI: 10.1111/jcmm.15970
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid (FA) protects human retinal pigment epithelial cells from H2O2‐induced oxidative injuries

Abstract: The aim of present study is to investigate whether Ferulic acid (FA), a natural polyphenol antioxidant, was able to protect ARPE‑19 cells from hydrogen peroxide (H2O2)‑induced damage, and elucidate the underlying mechanisms. Our results revealed that FA pre‐treatment for 24 hours can reverse cell loss of H2O2‐induced ARPE‐19 cells via the promotion of cell proliferation and prevention of apoptosis, as evidenced by 5‐ethynyl‐2′‐deoxyuridine (EdU) incorporation and terminal deoxynucleotidyl transferase‐mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In fact, different concentrations of H 2 O 2 have different effects on cells. More than 200 μ M of hydrogen peroxide induces apoptosis in endothelial cells, smooth muscle cells, and epithelial cells [ 29 ] [ 30 , 31 ]. Tong et al reported that low level of H 2 O 2 significantly promoted endothelial cell proliferation, migration, and tube formation; the mechanism is related to Nox-derived ROS [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, different concentrations of H 2 O 2 have different effects on cells. More than 200 μ M of hydrogen peroxide induces apoptosis in endothelial cells, smooth muscle cells, and epithelial cells [ 29 ] [ 30 , 31 ]. Tong et al reported that low level of H 2 O 2 significantly promoted endothelial cell proliferation, migration, and tube formation; the mechanism is related to Nox-derived ROS [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…FA protects epithelial cells from oxidative damage induced by H 2 O 2 . 11 It has been reported that FA improves myocardial I/R injury through succinate dehydrogenase-dependent antioxidant activity. 12 Moreover, FA also activates AMPK to produce an anti-inflammatory function.…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid (3-methoxy-4-hydroxycinnamic acid, FA) is a phenolic acid widely distributed in abundant grains, vegetables and plants such as Angelicae Sinensis Radix , Ligusticum Chuanxiong Rhizoma and Cimicifuga racemose ( Oliveira et al, 2019 ). It also exhibits a broad spectrum of biological activities, including repairing mitochondrial dysfunction ( Luo et al, 2020 ), anti-oxidant ( Xie et al, 2020 ), enhancement of immune function ( Kohno et al, 2020 ) and preventing epithelial-mesenchymal transition ( Ali et al, 2021 ). Several recent studies further provided evidence for the hepatoprotective effects of FA.…”
Section: Introductionmentioning
confidence: 99%